2004
DOI: 10.1080/02841850410003329
|View full text |Cite
|
Sign up to set email alerts
|

Radiological spectrum of late sequelae of corrosive injury to upper gastrointestinal tract. a pictorial review

Abstract: Barium examination of the upper GI tract is useful in the evaluation of late sequelae of corrosive injury (acid/alkali). There was no difference in the radiological findings as to the type of corrosive ingested. Thus, contrary to general belief, we found that acid and alkali damage both the esophagus and the stomach with equal degree of severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
24
0
4

Year Published

2006
2006
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 11 publications
1
24
0
4
Order By: Relevance
“…But the findings of an Indian study conducted by Zargar aet al are consistent with our study which reports the use of different types of acids in all cases (16). Indian data are strikingly different; the majority of ingestions are due to acids (17)(18)(19) as these are more easily available…”
Section: Discussion Discussionsupporting
confidence: 90%
“…But the findings of an Indian study conducted by Zargar aet al are consistent with our study which reports the use of different types of acids in all cases (16). Indian data are strikingly different; the majority of ingestions are due to acids (17)(18)(19) as these are more easily available…”
Section: Discussion Discussionsupporting
confidence: 90%
“…Patients with a high pretest probability of complex (tortuous) stricture (eg, history of caustic ingestion or radiation therapy) should be referred for a barium contrast esophagram as the initial test. After the barium esophagram, upper endoscopy is indicated to determine the underlying cause, exclude malignancy, and perform therapy (eg, dilation) if needed [1][2][3][4][5][6][7][8][9][10].…”
Section: Discussionmentioning
confidence: 99%
“…Studying x‐rays of patients who ingested caustic agents, Nagi et al 7 observed that both acid and alkali produced equally serious stenosis injuries. This is not what we have observed in daily practice, because alkali is more corrosive.…”
Section: Discussionmentioning
confidence: 99%